Stereoselective Palladium‐Catalyzed C(sp3)−H Mono‐Arylation of Piperidines and Tetrahydropyrans with a C(4) Directing Group. Issue 8 (10th March 2022) - Piticari, Amalia‐Sofia; Antermite, Daniele; Higham, Joe I.; Moore, J. Harry; Webster, Matthew P.; Bull, James A.
Abstract: A selective Pd‐catalyzed C(3)−H cis ‐functionalization of piperidine and tetrahydropyran carboxylic acids is achieved using a C(4) aminoquinoline amide auxiliary. High mono‐ and cis ‐selectivity is attained by using mesityl carboxylic acid as an additive. Conditions are developed with significantly lower reaction temperatures (≤50 °C) than other reported heterocycle C( sp 3 )−H functionalization reactions, which is facilitated by a DoE optimization. A one‐pot C−H functionalization‐epimerization procedure provides the trans ‐3, 4‐disubstituted isomers directly. Divergent aminoquinoline removal is accomplished with the installation of carboxylic acid, alcohol, amide and nitrile functional groups. Overall, fragment compounds suitable for screening are generated in 3–4 steps from readily‐available heterocyclic carboxylic acids. Abstract :